Outsourcing and technological innovations: a firm-level analysis - Ann Bartel; Saul Lach; Nachum Sicherman (Institute for the Study of Labor (IZA), 2008)
This paper presents a dynamic model that analyzes how firms' expectations with regards to technological change influence the demand for outsourcing. We show that outsourcing becomes more beneficial to the firm when technology is changing rapidly. As the pace of innovations in production technology increases, the firm has less time to amortize the sunk costs associated with purchasing the new technologies. This makes producing in-house with the latest technologies relatively more expensive than outsourcing. The model therefore provides an explanation for the recent increases in outsourcing that have taken place in an environment of increased expectations for technological change. We test the predictions of the model using a panel dataset on Spanish firms for the period 1990 through 2002. The empirical results support the main prediction of the model, namely, that all other things equal, the demand for outsourcing increases with the probability of technological change.
Keywords: O33; 330; Technological change; outsourcing; Technischer Fortschritt; Innovation; Sunk Costs; Outsourcing; Verarbeitendes Gewerbe; Spanien